If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 51 + -9 + -6 = v Combine like terms: 51 + -9 = 42 42 + -6 = v Combine like terms: 42 + -6 = 36 36 = v Solving 36 = v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 36 + -1v = v + -1v Combine like terms: v + -1v = 0 36 + -1v = 0 Add '-36' to each side of the equation. 36 + -36 + -1v = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -1v = 0 + -36 -1v = 0 + -36 Combine like terms: 0 + -36 = -36 -1v = -36 Divide each side by '-1'. v = 36 Simplifying v = 36
| k+10=-3 | | HX=WQx | | P=5L-4W | | (4-i)-(7+2i)= | | x^4-16x^3=y^3 | | 4m-12=91+5m | | y-(-1)=-5 | | -4n+5=1-3n | | h=-16t^2+88t | | 3/4x-2=1 | | 6x+158=8x+188 | | 19=2x+11 | | -22d-3d=2d+d-3d | | 9/8X3/5 | | 1/2x13=9 | | 1+2n+3n=9+4n | | 6x+7=4x+2x | | 2w-4=8 | | 6-10n=36 | | -6i*6i= | | 6C-7=0 | | 2x(4x-5)=20 | | 72=180-2z | | .75x+.5y=1.25 | | 1=6+96x-16x^2 | | m-10=3.3 | | .75y+.5x=1.25 | | 2(x-8)-3x(x+2)=-24 | | 5(3/4x−1)=2x | | 1/2(20-4x)=5x-2 | | .5x+.75y=1.25 | | 1/2x-13=11 |